Punishment and Penance : Two Phases in the History of the Bishop's Tribunal of Novara - Deutscher, Thomas Brian, 1949- (Book collections on Project MUSE., 2012)
Punishment and Penance provides the first comprehensive study of an Italian bishop's tribunal in criminal matters, such as violence, forbidden sexual activity, and offenses against the faith. Through numerous case studies, Thomas B. Deutscher investigates the scope and effectiveness of the early modern ecclesiastical legal system.Deutscher examines the records of the bishop's tribunal of the northern Italian diocese of Novara during two distinct periods: the ambitious decades following the Council of Trent (1563-1615), and the half-century leading up to the French invasions of 1790s. As the state's power continued to rise during this second time span, the Church was often humbled and the tribunal's activity was much reduced.Enriched by stories drawn from the files, which often allowed the accused to speak in their own voices, Punishment and Penance provides a window into the workings of a tribunal in this period.